From Microenvironment Remediation to Novel Anti-Cancer Strategy: The Emergence of Zero Valent Iron Nanoparticles - Ya-Na Wu; Li-Xing Yang; Pei-Wen Wang; Filip Braet; Dar-Bin Shieh (MDPI AG, 2022)
Accumulated studies indicate that zero-valent iron (ZVI) nanoparticles demonstrate endogenous cancer-selective cytotoxicity, without any external electric field, lights, or energy, while sparing healthy non-cancerous cells in vitro and in vivo. The anti-cancer activity of ZVI-based nanoparticles was anti-proportional to the oxidative status of the materials, which indicates that the elemental iron is crucial for the observed cancer selectivity. In this thematic article, distinctive endogenous anti-cancer mechanisms of ZVI-related nanomaterials at the cellular and molecular levels are reviewed, including the related gene modulating profile in vitro and in vivo. From a material science perspective, the underlying mechanisms are also analyzed. In summary, ZVI-based nanomaterials demonstrated prominent potential in precision medicine to modulate both programmed cell death of cancer cells, as well as the tumor microenvironment. We believe that this will inspire advanced anti-cancer therapy in the future.